Lung cancer chemotherapy, new treatment and related patents - Cheepsattayakorn,A. (Bentham Science Publishers B.V., 2015)
The majority of patients with lung cancer present with advanced stage which contributes to death of more people than any other malignancy in the world. The discovery of a number of lung cancer-molecular alterations contributes to uniquely targeted therapies with specific inhibitors for non-small cell lung cancer such as erlotinib, gefitinib and crizotinib. Pemetrexed has statistically shown significantly reduced adverse side effects of drug compared with docetaxel. V1801, an analog of gefitinib may overcome gefitinib resistance in patients with non-small cell lung cancer. Thymosin α1, an immunomodulator significantly improves patient's quality of life by enhancing T-cell function, stimulation of T-cell maturation and differentiation. Various novel compounds and chemotherapeutics were introduced in 2013 patents such as taxane, quinazoline, arylamino purine, benzodiazepine, pyrrolopyrimidine, nitrobenzamide, cyclopropane amide, 4-iodo-3-nitrobenzamide, heteroaryl (alkyl) dithiocarbamate, and histone deacetylase in treating non-small-cell lung cancer and piperidine, piperazine, picoplatin, and arsenic trioxide in treating small-cell lung cancer. © 2014 Bentham Science Publishers.